Antibody modulation: Limiting the efficacy of therapeutic antibodies. (September 2015) - Vaughan, Andrew T.; Cragg, Mark S.; Beers, Stephen A.
Graphical abstract: Abstract: Monoclonal antibodies (mAb) have revolutionised the way in which we treat disease. From cancer to autoimmunity, antibody therapy has been responsible for some of the most impressive clinical responses observed in the last 2 decades. A key component of this success has been their generally low levels of toxicity, and unique mechanisms of action. These two facets have allowed them to (a) be integrated rapidly into clinical practice in combination with conventional radio- and chemo-therapies and (b) to avoid the resistance mechanisms typically observed with classical small molecule drugs, such as upregulation of drug efflux transporters, dysregulation of apoptosis and mutations in key target enzymes/pathways. Although success with mAb therapies has been impressive, they are also subject to their own resistance mechanisms. In this perspective we discuss the various ways in which mAb therapeutics can be inhibited, concentrating mainly on the ways in which they can be removed from the target cell surface—a process called modulation. This can be achieved either in a cis-fashion on a single cell or in trans, precipitated by engagement with a second phagocytic cell. The evidence for each of these processes will be discussed, in addition to possible therapeutic strategies that might be employed to inhibit or reverse them.